The Development of Indonesian Language Teaching Materials for Class VII Semester 1 Based on North Sumatran Local Wisdom and the Digitization of Learning - Syamsul Arif; Tangson R. Pangaribuan; Rosdiana Siregar; Ahmad Nur Cahyo; Siti Nurjanah; Rolando Napitupulu (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to develop teaching materials for Indonesian class VII SMP in semester 1 based on local wisdom of North Sumatra and the digitization of learning. The teaching materials that will be developed are descriptive text, narrative story text, and procedure text. This study uses the Research & Development method referring to the research design with the stages of analyzing the needs of teaching materials based on local wisdom, data collection, product design, validation and testing. Product assessment is based on material quality, language quality, and media quality, as well as testing as student responses. The results of the research show that: (1) the results of the validation of the material experts indicate that the learning materials are declared feasible and "valid" with an average percentage gain of 87.8% with the criteria of "very good". Furthermore, the results of the validation of linguists showed that the language used in the learning materials was declared feasible and "valid" with an average percentage gain of 87.5% with the criteria of "very good". Then the results of the media validation showed that the media was deemed feasible and "valid" with the acquisition of a percentage of 92.2% with the criteria of "very good". (2) the results of the trial on junior high school students obtained an average percentage of 90.17% with very good criteria. The results of the percentage of trials carried out show that the Indonesian language learning materials for class VII SMP Semester 1 based on local wisdom of North Sumatra and their digitalization are appropriate and "valid" to be used as learning materials, especially in learning description texts and narrative texts for class VII semester 1 students.